East Asia's growing demand for primary commodities - macroeconomic challenges for Latin America - Gottschalk, Ricardo (UN New YorkUS, 2006)
Analyzes the macroeconomic impact of East Asia's growing demand for primary and industrial commodities in four Latin American countries - Brazil, Chile, Peru and Venezuela. Shows that while the export boom has contributed to improved external accounts in these countries, it has posed the challenges of how to manage the surpluses. Concludes that Latin American countries should do more to increase investment, especially in the infrastructure sectors. They should also avoid excessive currency appreciation.